COMMUNITY STRUCTURE OF FORAMINIFERA IN SURFACE SEDIMENTS AND CORRELATION WITH ENVIRONMENTAL CONDITIONS IN OFFSHORE WATERS OF BALIKPAPAN, MAKASSAR STRAIT - Suhartati M. Natsir; Aulya Firman; Indah Riyantini; Isni Nurruhwati (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
The distribution of foraminifera is influenced by several environmental factors such as depth, sediment type, chemical and physical oceanographic paramaters, and season. The aim of the study was to determine the foraminiferal assemblages and their relationship to physical and chemical parameters in the offshore of Balikpapan waters of Makassar Strait such as depth, temperature, currents, sediment types, and salinity. Surface sediment, physical, and chemical parameters sampling was conducted in April 2012. The results of the observations on the sediment samples recognized planktonic foraminifera in 6 genera and 40 genera of benthic foraminifera from the 6 stations. Biodiversity of planktonic foraminifera was categorized in a low category with a range of 0.198-0.525. However, biodiversity for benthic foraminifera was categorized in a high category with a range of 0.811-0.925. Dominance of planktonic foraminifera was medium to high with range of 0.474-0.802 which was assumed due to the sampling sites as an open waters. Meanwhile, dominance for benthic foraminifera was in a low category with range of 0.075-0.189. The most common planktonic foraminifera was found from Genus Globigerina (10538 individuals). While, the most abundant of benthic foraminifera was found from Genus Amphistegina (3134 individuals).  Keywords: abundance, foraminifera, sediment, and Makassar Strait